Antioxidant Activity and Oxidative Stress-Oriented Apoptosis Pathway in Saccharides Supplemented Cryopreserved Sperm of Pacific Abalone, Haliotis discus hannai - Shaharior Hossen; Zahid Parvez Sukhan; Yusin Cho; Won Kyo Lee; Kang Hee Kho (MDPI AG, 2022)
The Pacific abalone Haliotis discus hannai is a highly commercialized seafood in Southeast Asia. The aim of the present study was to determine the antioxidant activity and oxidative stress-oriented apoptosis pathway in saccharides supplemented cryopreserved sperm of Pacific abalone. Cryopreserved sperm showed impaired antioxidant defenses due to the reduced mRNA abundance of antioxidant genes (CAT, Cu/Zn-SOD, Mn-SOD, GPx, GR, and BCL-2), apoptosis inhibitor (HSP70, and HSP90) gene, and enzymatic antioxidant activity compared to fresh sperm. Such impaired antioxidant defenses caused an increase in the mRNA expression of apoptosis genes (Bax, and Caspase-3), finally leading to apoptosis. The impaired antioxidant defense also increased O2•− production and lipid peroxidation (MDA) levels, which further accelerated apoptosis. Considering all the experimental findings, an apoptosis pathway of cryopreserved sperm has been adopted for the first time. Specifically, sperm cryopreserved using 3% sucrose combined with 8% dimethyl sulfoxide (DMSO) showed improved mRNA stability, enzymatic activity, and DNA integrity with reduced O2•− production and MDA levels compared to sperm cryopreserved with the other types of examined cryoprotectants (8% ethylene glycol + 1% glucose, 6% propylene glycol + 2% glucose, 2% glycerol + 3% glucose, and 2% methanol + 4% trehalose). The present study suggests that 3% sucrose combined with 8% DMSO is suitable to cryopreserve the sperm of this valuable species for molecular conservation.